2018
DOI: 10.13040/ijpsr.0975-8232.9(3).1268-73
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:In this study, the stomach environment of paracetamol and metaclopramide active substances was prepared with the aid of chemometric method and UV spectrophotometer and their concentrations were measured at certain ratios. Spectra of these two active substances were observed separately in UV spectroscopy at different concentrations. Spectra of paracetamol and metaclopromide were observed by UV spectroscopy at certain ratios and concentrations. These observed spectra gave us an idea by using the chemome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The literature review focused on analytical methods for estimating PAR, ACE, and ES concluded that no analytical methods for estimating PAR, ACE, and ES concurrently were revealed. However, few chemometric aided UV spectrophotometric methods [2][3][4][5][6][7] were reported for PAR and ACE in combination with other drugs. The rationale of the present work aims to develop eco-friendly, simple UV spectrophotometric and chemometric methods Principal Component regression (PCR) and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review focused on analytical methods for estimating PAR, ACE, and ES concluded that no analytical methods for estimating PAR, ACE, and ES concurrently were revealed. However, few chemometric aided UV spectrophotometric methods [2][3][4][5][6][7] were reported for PAR and ACE in combination with other drugs. The rationale of the present work aims to develop eco-friendly, simple UV spectrophotometric and chemometric methods Principal Component regression (PCR) and drugs.…”
Section: Introductionmentioning
confidence: 99%